Integrating dosimetric and clinical insights: correlating acute bone marrow toxicity with irradiated marrow volume in rectal cancer patients undergoing concurrent chemoradiation - S., Divya; C. K., Kunhalankutty; C. C., Prasanth (International Journal of Research in Medical Sciences, 2024)
Background: Concurrent chemoradiation is one of the major treatments for locally advanced rectal cancer. As radiation therapy suppresses the bone marrow, it is essential to quantify the dose received by the pelvic bone marrow (PBM), which constitutes about 50% of the hematopoietic bone marrow. Methods: A prospective study conducted in 50 patients with locally advanced rectal cancer treated with long course concurrent chemoradiation. All the patients were followed up with weekly complete blood count for assessing hematological toxicities and were graded. PBM was contoured and subdivided into ilium bone marrow (IBM), lower pelvis bone marrow (LPBM) and lumbosacral bone marrow (LSBM). Volumes of bone marrow receiving different doses were quantified. Results: Among the 50 patients, 40 (80%) developed acute bone marrow toxicity, during the course of treatment. Highest grade of bone marrow toxicity developed in 20 (40%) patients which was grade 2. Compared to grade 1, grade 2 neutropenia patients exhibited significantly higher levels of V10 to V40 (p<0.05) in PBM and significantly higher levels of V20 in IBM and LSBM. In LPBM, compared to grade 1 leukopenia and neutropenia, grade 2 leukopenia and neutropenia exhibited significantly higher levels of V10 and V20 (p<0.05). Conclusions: Increased PBM V10 to V40, IBM V20, LSBM V20, LPBM V10 and V20 were significantly related to the higher grades of neutropenia in locally advanced rectal cancer patients undergoing long course concurrent chemoradiation. Increased LPBM V10 and V20 were also significantly related with higher grades of leukopenia.